The relationship between ingroup identity and Paranoid ideation among people from African and African Caribbean backgrounds. (19th November 2019) - McIntyre, Jason C.; Elahi, Anam; Barlow, Fiona Kate; White, Ross G.; Bentall, Richard P.
Abstract : Objectives: People from ethnic minority groups experience higher rates of paranoid delusions compared with people from ethnic majority groups. Identifying with social groups has been shown to protect against mental health symptoms; however, no studies have investigated the relationship between social identification and paranoia in ethnic minority populations. Here, we investigated the association between British identification and paranoia in a sample of people from African and African Caribbean backgrounds living in the United Kingdom. We also assessed the role of potential mediating (self‐esteem and locus of control) and moderating (contact with White British people) factors. Design: Cross‐sectional quantitative survey design. Methods: We recruited 335 people from African and African Caribbean backgrounds who completed online self‐report measures of identification with Great Britain, self‐esteem, locus of control, positive and negative contact with White British people, and paranoia. Results: A parallel moderated mediation model indicated that British identification was associated with lower paranoia when participants experienced primarily positive contact with White British people. British identification was associated with higher paranoia when participants had primarily negative contact with White British people. Both effects were mediated by changes in locus of control, but self‐esteem was not implicated in either pathway. Conclusions: Identification with the majority culture is associated both positively and negatively with paranoid beliefs depending on the types of social interactions people experience. The findings have implications for preventative social prescribing initiatives and for understanding the causes of the high rates of psychosis in ethnic minority populations. Practitioner points: People from African and African Caribbean backgrounds experience high rates of paranoia, which may stem from social causes such as lack of belonging and negative social experiences. Among people from African backgrounds living in the UK, British identification is associated with lower paranoia when people's social experiences with White British people are positive and higher paranoia when their social experiences with White British people are negative. It is recommended that social interventions designed to reduce paranoia in vulnerable groups foster positive social contact and community belonging, which should enhance feelings of personal control. Understanding the complex interplay between social identity and social contact in the development of paranoia may help therapists and researchers better understand the phenomenology and risk factors of paranoid symptomology.